A smartphone-assisted ratiometric colorimetric and fluorescent probe for triple-mode determination of nitrite based on MnO2 nanoparticles and carbon quantum dots. (1st June 2023) - Peng, Bo; Wang, Chunjuan; He, Xueyan; Ma, Yongjun; Zhou, Min; Ma, Xin; Zhao, Shengguo; Fang, Yanjun
Graphical abstract: Highlights: Triple mode detection of nitrite based on MnO2 NPs and CQDs were developed. The ratiometric absorbance of dual wavelength was employed in the spectrophotometry. A free APP PhotoMetrix was used for smartphone-based colorimetry. The proposed method performed well in high-salt samples without pretreatment columns. The proposed method was validated with standard Griess spectrophotometric method. Abstract: A triple-mode colorimetric and fluorescent sensing scheme based on manganese dioxide nanoparticles (MnO2 NPs) and carbon quantum dots (CQDs) were developed to determine nitrite. MnO2 NPs can oxidize 3, 3′, 5, 5′-tetramethylbenzidine (TMB) into a blue oxidation product (TMBox), which is further oxidized into a yellow diimine derivative by nitrite. The ratio of absorbance at 652 nm to 452 nm was monitored as signal response for UV–vis detection mode. A "turn-off" CQDs fluorescence probe was also constructed for fluorescent detection mode. Smartphone tool kit was used to capture the color of sample for smartphone-based measurement. Various analytical performance under different detection modes were obtained and compared. The proposed methods were applied to food samples with satisfactory recoveries (83.3–106 %). The results were validated with AOAC standard spectrophotometric method. The current triple-mode detection were accurate, convenient, low-cost and fast for analyzing nitrite in foods and water samples on-site.